Determinación de los factores que potencian la ventaja competitiva de la industria aeroespacial del estado de Chihuahua, México - Manzo Martínez, Lizet (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The present work has the purpose to determine if the strategic alliances, the knowledge, the activity of investigation and development (I&D), the quality and the cost allow a competitive advantage to the companies of the aerospace industry Of Chihuahua. The study is based on the theory of competitive advantage (VC) and the theory of Resource-Based View (RBV), which allows to understand the causality between competitive advantage and strategic alliances, knowledge, research and development activity (R & D), quality and cost. For this work, a survey is applied as an instrument to determine the most representative elements that allow a competitive advantage. The SPSS software was used to describe each of the variables and to determine which are the most representative and which are the least representative to generate competitive advantages. The Forgotten Effects (EO) model is used as an alternative method to determine the relationship between the variables and the effects that were forgotten by some circumstance but that are representative. It concludes by demonstrating whether the variables strategic alliances, knowledge, R & D activity, quality and cost are sources of competitive advantage for national and foreign companies in the aerospace industry in Mexico.

The present work has the purpose to determine if the strategic alliances, the knowledge, the activity of investigation and development (I&D), the quality and the cost allow a competitive advantage to the companies of the aerospace industry Of Chihuahua. The study is based on the theory of competitive advantage (VC) and the theory of Resource-Based View (RBV), which allows to understand the causality between competitive advantage and strategic alliances, knowledge, research and development activity (R & D), quality and cost. For this work, a survey is applied as an instrument to determine the most representative elements that allow a competitive advantage. The SPSS software was used to describe each of the variables and to determine which are the most representative and which are the least representative to generate competitive advantages. The Forgotten Effects (EO) model is used as an alternative method to determine the relationship between the variables and the effects that were forgotten by some circumstance but that are representative. It concludes by demonstrating whether the variables strategic alliances, knowledge, R & D activity, quality and cost are sources of competitive advantage for national and foreign companies in the aerospace industry in Mexico.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias en Negocios Internacionales
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2618; info:eu-repo/classification/cti/5; ININEE-D-2020-0544; Competitividad; Posicionamiento; Modelo de efectos olvidados